2018
DOI: 10.1104/pp.18.00634
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Plays an Essential Role in the Root’s Response to Osmotic Stress

Abstract: As SOSG fluorescence indicated the presence of singlet oxygen both before and after cell death, it is important to consider whether the appearance of singlet oxygen is an essential component of PEG-induced . Relationship between integrity of the quiescent center and root elongation. A, Fluorescence resulting from SCR::GFP expression in the endodermis and quiescent center. Roots were exposed to 30% PEG for 1 to 8 h and counterstained with propidium iodide (PI). The median plane was imaged where opaque regions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 55 publications
(26 reference statements)
2
34
0
Order By: Relevance
“…These results suggested that SMXL6, 7 and 8 genes were involved in the regulation of mechanisms associated with, at least, these investigated drought resistance-related traits. An increase in cell membrane integrity can help plants prevent leaf water loss as reported by various studies [55][56][57][58]. Furthermore, the higher leaf surface temperatures observed in smxl6,7,8 mutant plants in comparison with WT plants under both well-watered and water-deficit conditions supported the reduced leaf water transpiration from the smxl6,7,8 mutant versus WT plants (Figure 3a-c).…”
Section: Discussionsupporting
confidence: 70%
“…These results suggested that SMXL6, 7 and 8 genes were involved in the regulation of mechanisms associated with, at least, these investigated drought resistance-related traits. An increase in cell membrane integrity can help plants prevent leaf water loss as reported by various studies [55][56][57][58]. Furthermore, the higher leaf surface temperatures observed in smxl6,7,8 mutant plants in comparison with WT plants under both well-watered and water-deficit conditions supported the reduced leaf water transpiration from the smxl6,7,8 mutant versus WT plants (Figure 3a-c).…”
Section: Discussionsupporting
confidence: 70%
“…The vital stains Fluorescein diacetate (FDA, Sigma) and Propidium Iodide (PI, Sigma) were applied simultaneously as reported by 52 . Cell viability was also determined in SCR::GFP plants as reported by 53 . The fluorescent signals were detected by laser scanning confocal microscope -LSM710 (Zeiss) with a Plan-Apochromat 20 ×0.8 numerical aperture air objective lens.…”
Section: Methodsmentioning
confidence: 99%
“…Under soil drying conditions, this is impossible as soil Ψw changes continuously along with water evaporation and consumption by a plant. On the other hand, due to interference of PEG with root integrity [78], this equilibrium is also hardly achievable in aqueous PEG solutions (especially when PEG concentration is high). Thus, the agar-based model system currently is an ideal choice to address dehydration avoidance and mechanisms of dehydration tolerance [10].…”
Section: Agar-based Drought Modelsmentioning
confidence: 99%